PENGARUH PELAYANAN ADMINISTASI, SARANA PRASARANA, KINERJA PEGAWAI, DISIPLIN KERJA, MOTIVASI KERJA TERHADAP KEPUASAN MASYARAKAT PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL DI KOTA MEDAN - Jesica Oktavia br Panjaitan; Ega Trinanda Sianipar; Memorismen Telaumbanua; Yois Nelsari Malau; Niarita Bukit (Mount Hope Economic Global Journal, 2025)
The government defines public services as all forms of service activities carried out by government agencies at the central and regional levels and including other state-owned enterprises that provide goods or services both in order to fulfill the needs of the community and the implementation of statutory provisions. Facilities and infrastructure can also be called something that is most needed by every organization in order to achieve the expected goals, while performance is very necessary because from the criteria it can be seen how good the employee's ability is when providing services that can satisfy the community. Employees who have good performance are employees who are personally responsible for unlimited, firm and committed to existing risks. Work discipline is the level of the company to encourage awareness and the ability of all employees to obey all regulations that have been implemented according to applicable norms, and work motivation is the encouragement for someone to be able to carry out activities and channel their abilities in order to achieve goals for agencies and companies. The purpose of this study is to assess the quality of service, comfort, effectiveness, punctuality and responsibility of employees in their work when serving the community.